Liming and Nitrogen Effects on Maize Yield and Nitrogen Use Efficiency. Issue 16 (8th September 2019) - Victoria, Otie; Ping, An; Yang, Shao; Eneji, Egrinya
ABSTRACT: The study was aimed to determine the appropriate nitrogen (N) rate to combine with liming for enhanced maize yield and nitrogen use efficiency (NUE). Two maize varieties [Ikom White (IKW) and Obatanpa-98 (Oba-98)], two lime rates (0 kg ha −1 and 500 kg ha −1 ) and three N rates (0, 90 and 180 kg ha −1 ) were used. The treatments were laid as a split-split plot in a randomized complete block design with three replications. The growth attributes, photosynthetically active radiation (PAR), harvest index, dry matter, and grain yield increased ( P ≤ 0.05 ) with increases in N rates, especially in plots amended with lime. Oba-98 was better yielding (2.12 versus (vs) 1.88 t ha −1 ) and absorbed more ( P ≤ 0.05 ) radiation (442.06 vs 409.54 μmol m −2 s −1 ) than IKW. The efficiency indices and partial factor productivity were best optimized at the 90 kg ha −1 N rate with Oba-98 having higher values than IKW. Therefore, liming (500 kg ha −1 ) plus N at 180 kg ha −1 produced the best yield of the hybrid maize, Oba-98.